Enterprise-Wide Risk Management (EWRM) practices: Between corporate governance compliance and value creation - Ab. Wahab, Norlida; Kasim, Isahak; Hussin, Mohd Rasid (2010)
Although Enterprise-Wide Risk Management (EWRM) concept is still new in many parts of Asia, there are positive indications that EWRM is beginning to receive attention.As a matter of fact, this topic is being widely discussed on an industry-wide basis.The emergence of EWRM is cited to be driven most by corporate governance, and its effective implementation is claimed to contribute towards value creation.This paper thus examined the drivers and the success of EWRM implementation with corporate governance compliance and value creation in for-profit companies.A survey found that EWRM concepts and its efforts have become a growing concern among Public Listed Companies (PLCs).The motivation factor of corporate governance is evidenced especially in nonfinancial companies.Whilst financial companies cited that their EWRM practices were not only being driven by corporate governance compliance, but also for good business practice and improved decision making. In addition the motives of its implementation ensured the survival of the company and value creation.